ANALISIS FAKTOR SELF-EFFICACY DAN NORMA SUBJEKTIF DALAM PENERIMAAN SISTEM INFORMASI PEMBELAJARAN E-LEARNING - Ari Pambudi; Hani Dwi Ariessanti; Fata Nidaul Khasanah; Anggraeni Pratama Indrianto; Ikhsan Nurahman (Journal of Innovation And Future Technology, 2026)
Improvements in information technology have given rise to the phenomenon of using e-learning systems in education. However, the success of e-learning implementation is highly dependent on user acceptance. This research identifies factors that influence tertiary students' interest in using e-learning in Indonesia, by focusing on self-efficacy and subjective norms. By involving 116 respondents and analyzing data using PLS-SEM, this research shows that around 41.5% of the variability in interest in using e-learning can be explained by self-efficacy and subjective norms. The findings show that subjective norms have a greater influence than self-efficacy on interest in using e-learning. These results reinforce the importance of subjective norms as a major factor in e-learning acceptance. This research also highlights the need for further research to understand additional factors that may influence interest in using e-learning in the future.